The results of study of collection samples of spring soft wheat in the Middle Volga Region - I. F. Demina (Аграрная наука Евро-Северо-Востока, 2020)
During the research, there were studied 186 varieties of spring soft wheat of different ecological and geographical origin to develop valuable initial material for new varieties in the conditions of Middle Volga. The studies were carried out in accordance with the methodic recommendations of VIR. According to the duration of the growing season, the samples were divided into three groups: early ripening – 29.4 %, mid-ripening – 45.0 % and mid-late-ripening – 25.6 %. The largest number of high-yielding varieties belongs to the mid-ripening group. Five groups are distinguished according to plant height: above 120 cm – tall, 120-105 cm – medium-grown, 104-85 cm – undersized, 84-60 cm – semi-dwarfs, less than 60 cm – dwarfs. A group of semi-dwarfs showed high resistance to lodging. The yield of productive genotypes in this group is 192-210 g/m2. The analysis of the elements of the yield structure showed the varieties that exceeded the standard in the number of grains in the ear (32.8 pcs.): Annet (38.2 pcs.), Baganskaya 95 (36.5 pcs.), Riks (37.7 pcs.), Lubninka (36.8 pcs.), (Russia, West Siberian Region), Biryusa (37.2 pcs.) (Russia, East Siberian Region), by grain weight per ear – Russian varieties from East Siberian, West Siberian and Lower Volga Regions (0.96-1.52 g), and varieties of foreign selection from North America (0.89-1.64 г). According to the yield the following varieties significantly exceeded the standard variety Kinelskaya Niva (310 g/m2) by 30-54 g/m2 (LSD05 = 22.5 g/m2): Russian varieties Annet, Baganskaya 95, Lavrusha, Tarskaya 10, Pamyati Maistrenko, Omskaya 39, Duet (West Siberian region), Voevoda (Lower Volga region) and Uyarochka (East Siberian region), foreign varieties Aktyube 10 (Kazakhstan) and Granit (Canada). The varieties with complex resistance to the main types of leaf diseases (leaf rust and powdery mildew) have been identified: Norwell, Granit, Dandy, CDC Merlin (Kanada), Lavrusha, Tarskaya 10 (West Siberian Region), Tybalt (Netherlands), Voevoda (Lower Volga Region), Etyud (Ukraine). The identified varieties were used as parental forms in crosses.